Study protocol: an investigation of mother-infant signalling during breastfeeding using a randomised trial to test the effectiveness of breastfeeding relaxation therapy on maternal psychological state, breast milk production and infant behaviour and growth - Shukri, N. H. M.; Wells, Jonathan C. K.; Mukhtar, Fahad; Lee, M. H. S.; Fewtrell, Mary S. (BioMedical Central, 2017)
Background: The physiological and psychological signalling between mother and infant during lactation is one of the prominent mother-infant factors that may influence breastfeeding outcomes. The infant can ‘signal’ his needs through vocalisation, and the mother can respond by allowing or restricting nipple access, which might alter the breast milk composition or volume. This may lead to parent-offspring conflict during the lactation period. Challenging infant behaviour has also been associated with maternal psychological distress, which might affect breastfeeding performance. Most attempts to improve breastfeeding rates focus on providing additional support, yet many aspects of the breastfeeding process are poorly understood. Thus, our objective is to investigate mother-infant signalling during breastfeeding by manipulating maternal psychological state using a relaxation therapy intervention. The study will test the hypothesis that mothers who listen to the therapy will be more relaxed/less stressed and this will favourably alter breast milk composition and/or affect milk volume and hence influence infant outcomes. Methods: A randomised controlled trial will be conducted in first-time breastfeeding mothers and their new-born infants. Pregnant mothers will be recruited at antenatal clinics in Selangor, Malaysia, and four home visits will be carried out at 2, 6, 12 and 14 weeks postnatally. Participants will be randomised into a control and an intervention group in the early post-partum period. Mothers from the intervention group will be asked to listen daily to an audio recording with relaxation therapy during breastfeeding. Maternal psychological state, breastfeeding practices and infant behaviour will be assessed using validated questionnaires. Milk volume will be measured using stable isotopes. Breast milk samples will be collected to measure macronutrient content and hormone levels. Anthropometric measurements (weight, length and head circumference) will be performed during all home visits, including body composition at week 14. Discussion The main outcomes will be the effect of the intervention on maternal psychological state, milk production, cortisol levels, and infant behaviour and growth. Secondary outcomes will be associations between breast milk composition and infant appetite and growth. This study aims to provide a greater understanding of maternal-infant factors which influence breastfeeding outcomes and which may be useful targets for future interventions.